2006
DOI: 10.1353/mcb.2006.0095
|View full text |Cite
|
Sign up to set email alerts
|

Same Financial Development yet Different Economic Growth--Why?

Abstract: We re-study the relationship between financial development and real GDP per capita growth in 48 countries. What we find is an interesting evidence that only stock market development has positive effects on growth and that banking development has an unfavorable, if not negative, effect on growth. We examine whether or not these impacts are a product of various financial and economic conditional variables. Our conditional variables consist of financial liberalization, two sets of country development dummies, cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
183
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(198 citation statements)
references
References 63 publications
(69 reference statements)
12
183
1
2
Order By: Relevance
“…Beck and Levine (2004) find that both banks and stock markets promote economic growth in the panel data analysis. Chen and Lee (2006) find contradictory results in a cross-country study.…”
Section: Introductionmentioning
confidence: 91%
“…Beck and Levine (2004) find that both banks and stock markets promote economic growth in the panel data analysis. Chen and Lee (2006) find contradictory results in a cross-country study.…”
Section: Introductionmentioning
confidence: 91%
“…More directly related with the particular topic of banking development, Levine (2002) provided several arguments based on banks' relationships with large firms for which a negative association with aggregate development is perfectly feasible. More recently, Shen and Lee's (2006) results suggested that while the development of the stock market is always positive for growth, this is not the case for banking development, for which negative effects are found. These effects are also heavily influenced by conditioning factors such as geography, currency crisis and institutional quality, with differing moderation effects for countries at different stages of development.…”
Section: The Links Between Banking Integration and Economic Developmentmentioning
confidence: 99%
“…The banking system plays a fundamental role in economic development, and its safety and soundness over time generate important benefits for society (Shen and Lee, 2006;Beck, Demirgüç -Kunt, and Levine, 2010). Wu and Shen (2013) suggest that the nature of bank activity, characterized by the use of resources obtained from non-proprietary stakeholders, determines the obligation to provide feedback to the community more frequently than other industries.…”
Section: Corporate Social Responsibility In the Banking Sectormentioning
confidence: 99%